2007
DOI: 10.1152/ajplung.00121.2007
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of chloride channels in TGF-β1-induced apoptosis of human bronchial epithelial cells

Abstract: Widespread damage of airway epithelium and defective epithelial repair are hallmarks of chronic asthma. Growth factors and cytokines spatially and temporally regulate epithelial shedding and repair. Within this context, a key function is exerted by transforming growth factor (TGF)-beta. Recent growing evidence suggests that chloride (Cl(-)) channels are critical to cell apoptosis. We examined the effects of TGF-beta1 on Cl(-) channel expression and activity and its relationship with apoptosis in human bronchia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
2
19
0
1
Order By: Relevance
“…Calcium-activated chloride channel (CaCC) is the first chloride channel that was reported to be related to asthma. We also found that CLC-3 is involved in TGF-1 induced airway epithelial cell apoptosis [11]. It is reasonable to speculate that CLC might play an important role in the proliferation, apoptosis and migration of immune cells such as T cells, neutrophils, eosinophils and monocytes.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Calcium-activated chloride channel (CaCC) is the first chloride channel that was reported to be related to asthma. We also found that CLC-3 is involved in TGF-1 induced airway epithelial cell apoptosis [11]. It is reasonable to speculate that CLC might play an important role in the proliferation, apoptosis and migration of immune cells such as T cells, neutrophils, eosinophils and monocytes.…”
Section: Introductionsupporting
confidence: 58%
“…Cell volume reduction may play a mechanistic role in apoptosis, since hypertonic medium induces or potentiates apoptosis in some studies, and decrease in the regulatory volume induces enhanced responses in HeLa cells, U937, PC12 and NG108-15 cells undergoing apoptosis [64]. We observed that TGF-1 significantly induced human bronchial epithelial cell (HBEC) apoptosis, which paralleled a significant decrease in the endogenous expression of CLC-3 protein and mRNA transcripts [11]. Outwardrectifying and voltage-dependent CLC-3-like Cl -currents in human bronchial epithelial cells were diminished by TGF-1 stimulation [11].…”
Section: Epithelial Cellsmentioning
confidence: 85%
“…These results provide the first and compelling evidence that ClC-3 is critically linked to preadipocyte apoptosis induced by saturated FFA in vitro and in T2DM. ClC-3 has been suggested to be essential for apoptosis in a variety of cell types, such as vascular smooth muscle cells [19,34], endothelial progenitor cells [21], tumor and carcinoma cells [38,39] and bronchial and intestinal epithelial cells [20,40,41], and thus may play roles in the disease processes of hypertensive vascular remodeling [19], inflammatory responses [20] and tumor cell death [38]. Our presented data demonstrated that ClC-3 protein expression and cellular apoptosis in preadipocytes could be significantly increased in response to saturated FFAs (palmitate), but not unsaturated FFAs.…”
Section: Discussionmentioning
confidence: 99%
“…In one batch, HUVECs were exposed to DMEM containing different glucose concentrations (5.5, 17.8, 35.6, 71.2 and 142.4 mmol/l, respectively, pH = 7.40) or 35.6 mmol/l of mannitol (as a control for osmotic pressure) for indicated times (12,24,48,72,120, and 168 h, respectively) to explore an optimal glucose concentration and treatment time. In another parallel batch of the experiment, HUVECs were separately pretreated for 2 h with DIDS (100 lmol/l), 9-anthracenecarboxylic acid (9-AC, 1 mmol/l), bumetanide (BUM, 50 lmol/l), or Cl --free media (Cl -was replaced with gluconate -) (Cl -free), and then exposed to 35.6 mmol/l of glucose for 48 h. HUVECs, which were only exposed to the media containing 5.5 or 35.6 mmol/l of glucose for 48 h, were considered as Control or HG group, respectively.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Chloride ion (Cl -) is extensively involved in electrophysiological activity, cell volume, intracellular pH (pHi), and immune response [12][13][14]. In the past decade, the roles of Cl -in cell proliferation, differentiation and apoptosis have been highly concerned [15][16][17].…”
Section: Introductionmentioning
confidence: 99%